Hoffa fractures (corona/ fractures) of the femoral condyle. A case report - Armis, Armis (Universitas Gadjah Mada, 1997)
Hoffa Fracture is a fracture at femoral condyle caused by direct injury of the knee at flexion position; there fore the articular surface is broken. Distal fragment of fracture can be displaced or undisplaced. The Hoffa fracture is divided into three types according to prognostic implication. Type I, the intra articular fracture line reaches the supracondyle of the femur and some of the soft tissues still attached to the distal fragment. Type II, intra articular fracture without any attachment of the soft tissue to the distal fragment. and type III where the fracture line slight anteriorly and proximally to the condyle of the femur with some attachment of the soft tissues and ligaments to the distal fragment. A case of young motor cyclist who involved in collision against a bridge is reviewed. He has type I Hoffa fracture Which is equal to grade III B Gustilo classification system. The conservative procedure of open wound management and skeletal traction was adequate. The problem was that, the radiographic interpretation was difficult if the anterior part of the femoral condyle was intact, undisplaced or slightly displaced. Therefore CT-Scan and tomography were indicated. In type I and type III Hoffa fracture, some soft tissue structures remain attached to the distal condyle fragment and that there will be some blood supply to this fragment. However, in type II fracture the soft tissue may completely be unattached especially type II C and it could predispose to avascular necrosis or nonunion.Key Words : Fracture - intraarticular - femoral condyle - avascular necrosis - non-union